"Spatial Distribution of Colleges of Education and Effects on the Forest Ecosystem: A Case Study of College of Education Ikere, Nigeria" (2014)
Distribution of various Colleges of Education in Nigeria was examined. The list of Colleges of Education in the country was obtained from National Commission for Colleges of Education (NCCE) and their respective coordinates were obtained. Satellite imagery of Ikere forest reserve was obtained from Google earth while the sketch map was obtained from Ekiti State Department of Forestry (ESDF). Photographs of some parts of the forest reserve were taken. A set of 50 questionnaire was administered by the old staff of the College of Education, Ikere – Ekiti. The coordinates of various Colleges of Education obtained were loaded into ArcGIS to represent their locations on the map of Nigeria. Federal Colleges were represented with points, state colleges were represented with asterisks while private colleges were represented with upward arrows. All the attribute data obtained for Ikere forest reserve were used to generate a digital map showing the extent of all the various land use within the forest ecosystem. Various forest types were represented with polygons of different shapes and colours. Roads of different types were represented with lines of different sizes. Photographs of some parts of the forest reserves were hotlinked to reveal the actual status on the land. Administered questionnaire was coded and analyzed appropriately. It was discovered that the Colleges of Education established by the State Government were more (56.63%) than those established by the Federal Government (26.51%) while the private ownership established the least Colleges of Education (16.87%) in the country. When the spatial distribution of Colleges of Education by geopolitical zones were examined, South-West recorded the highest number (21.69%), followed by North-East (20.48%), South South (15.66%), North Central (14.46%), in that order and the least was recorded in South-East (13.25%). Forest in its natural status in Ikere forest reserve have been reduced to mere farmland, degraded land and encroached plantation of Gmelina arborea and Tectona grandis, which was not the case before the inception of the College. Old staff of College of Education Ikere Ekiti was responsible for the level of depletion of the forest reserve.